PERUBAHAN TATA GUNA LAHAN TERHADAP DAYA DUKUNG FUNGSI LINDUNG DAERAH ALIRAN SUNGAI (DAS) BABON DI SEMARANG DAN SEKITARNYA - Nugraha, Bachtiar Rama Ardhi; Suryaningrum, Irnanda; Amanda, Putri; Agfanisa, Rahma; Ardeny, Anisa Nur Faizah; Pratama, Liona Surya; Haris, Amnan; Fariz, Trida Ridho; Jabbar, Abdul; Kholil, Putri Alifa; Faizah, Nur (Jurnal Riptek, 2025)
This study aims to analyze the impact of land use changes on the carrying capacity of the protective function of the Babon Watershed (DAS Babon) and its relation to flood events in the area. The research employs a quantitative approach using satellite imagery data from 2015 and 2023, processed with Geographic Information Systems (GIS) to map land use changes and the carrying capacity of the watershed's protective function. The results indicate significant land use changes, particularly the conversion of agricultural land into residential and industrial areas, which has reduced the extent of water infiltration zones and natural vegetation. The decline in the carrying capacity of the protective function of the Babon Watershed has increased flood risks, especially in downstream areas exposed to high surface runoff. The analysis of the protective function's carrying capacity (DDL) reveals a degradation in protective quality in several districts, with lower DDL values observed in 2023. The use of impervious materials such as concrete and asphalt exacerbates drainage quality and worsens flood risks.